On a boundary value problem to third order PDE with multiple characteristics - Apakov, Yusufjon P. P.; Rutkauskas, Stasys (Nonlinear Analysis: Modelling and Control, 2011)
In the paper the second boundary value problem in a rectangular domain to equation uxxx − uyy = f(x, y) with the multiple characteristics is considered. The considered equation is closely related with nonlinear equation uxxx + uyy −(ν/y)uy = uxuxx, which describes transonic flow of a gas around a revolution bodies. Using the fundamental solutions of corresponding homogeneous equation the Green function of analyzed problem is composed and thereby this problem is solved.